Optimization of the Performance of a Microplate Type UV-Vis Spectrophotometer as a Protein Content Testing Instrument Based on Green Analytical Chemistry (GAC) - Martin Sulistyani; Mahatmanti, F. Widhi; Huda, Nuril; Prasetyo, Ridho (Prodi Kimia, 2025)
Advancements in laboratory technology have driven the adoption of more efficient and environmentally friendly analytical methods, in line with the principles of Green Analytical Chemistry (GAC). This study aims to optimize the performance of a microplate-based UV-Vis spectrophotometer for determining protein content in food samples using the Biuret method. The method is based on a colorimetric reaction between Biuret reagent and peptide bonds in proteins, forming a purple complex whose absorbance is proportional to protein concentration. Three dilution methods were evaluated: mL-microplate, µL-microplate, and mL-cuvette, based on parameters including maximum wavelength, linearity, and accuracy. All methods showed the same maximum absorbance wavelength (562 nm), indicating reaction stability. The mL-cuvette method achieved the highest linearity (R² = 0.998), while the mL-microplate method demonstrated the best accuracy (91.00%) and most consistent results in tempeh and yogurt samples. Meanwhile, the µL-microplate method offered acceptable accuracy (90.25%) with significantly reduced reagent volume, supporting the GAC approach. Therefore, the mL-microplate method is recommended as the primary technique for protein analysis using UV-Vis spectrophotometry, while the µL-microplate method provides an efficient and eco-friendly alternative for modern laboratory applications.